A Classroom Exercise to Examine the Trade‐off between Mission Capacity and Life Cycle Cost. (January 2015) - Kang, Keebom; Doerr, Kenneth H.
ABSTRACT This article presents a classroom exercise, centered on a simulation that has been used for 4 years in an MBA program to help students develop an understanding of the trade‐offs involved in managing capital assets in the public sector. Though often ignored in business schools, mission is a key criterion that must be considered when managing such assets, and acts as a surrogate for profit. The case presents a rich environment in which the impact of cost reductions (or additional investments) on mission can be quantified, and trade‐offs can be assessed and discussed. It gives students a chance to develop creative ideas for process improvement, and provides sufficient data for them to analyze the impact of their suggestions in a rigorous way.